The investment arbitration in the new generation free trade agreements: a national analysis from the perspective of the right to an effective judicial remedy - Schumann Barragán, Guillermo (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper analyzes the mechanism for investor-State dispute settlement in the new generation free trade agreements from the perspective of the right to an effective judicial remedy. In particular, it examines the compatibility of the CETA investment arbitration with Articles. 47 CFREU, 6 ECHR and 24 of the Spanish Constitution
Keywords: investment arbitration; CETA; right to an effective judicial remedy; Art. 47 CFREU; Art. 24 CE; Art. 6 ECHR